Math games for middle school : challenges and skill-builders for students at every level - Salvadori, Mario George, 1907-1997; Wright, Joseph P., 1939- (Chicago Review Press, 1998)
"Uses explanations, word problems, and games to cover some mathematical topics that middle school students need to know, including the invention of numerical notations, basic arithmatical operations, measurements, geometry, graphs, and probability."
Obsahuje rejstřík
Keywords: matematika -- úlohy; matematické hry; studium a výuka; střední školy; mathematics -- problems, exercises, etc; mathematical recreations; study and teaching; secondary schools; příručky; handbooks and manuals